2021
DOI: 10.1051/0004-6361/202039673
|View full text |Cite
|
Sign up to set email alerts
|

A relation between the radial velocity dispersion of young clusters and their age

Abstract: The majority of massive stars (> 8 M⊙) in OB associations are found in close binary systems. Nonetheless, the formation mechanism of these close massive binaries is not understood yet. Using literature data, we measured the radial-velocity dispersion (σ1D) as a proxy for the close binary fraction in ten OB associations in the Galaxy and the Large Magellanic Cloud, spanning an age range from 1 to 6 Myr. We find a positive trend of this dispersion with the cluster’s age, which is consistent with binary harden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…The effects of migration on the binary period distribution will halt when the sinks of angular momentum disappear, via the dissipation of the disk or dispersal of the cluster, or as other protostellar bodies are pushed far out or are ejected. Additional evidence for this migration scenario was found by Ramírez-Tannus et al (2021), who show that the observed RV dispersion of stellar clusters positively correlates with their age.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The effects of migration on the binary period distribution will halt when the sinks of angular momentum disappear, via the dissipation of the disk or dispersal of the cluster, or as other protostellar bodies are pushed far out or are ejected. Additional evidence for this migration scenario was found by Ramírez-Tannus et al (2021), who show that the observed RV dispersion of stellar clusters positively correlates with their age.…”
Section: Introductionmentioning
confidence: 67%
“…In both accretion scenarios, competitive or core accretion, wide binaries are initially formed at large distances and eventually harden over time. Observing companions close to the primary star could also indicate that protostellar cores that were formed at the edges of the accretion disk migrated over time, as suggested by Oliva & Kuiper (2020) and Ramírez-Tannus et al (2021). This hardening process that may occur on timescales of the order of 2 Myr (Ramírez-Tannus et al 2021) might be driven by the interaction with the remnant of the accretion disk, in the context of disk fragmentation theories, or with other protostellar bodies present in the cluster.…”
Section: Connection With Star Formation Modelsmentioning
confidence: 96%
“…They may have been altered by early dynamical processing, through e.g., migration as suggested by recent results on the dearth of short-period systems in M17, one of the youngest massive star forming regions studied in depth (Ramírez-Tannus et al ( 2017), Sana et al (2017)). The early dynamical processing of the orbital properties is further supported by an observed correlation of the dynamical dispersion as a function of cluster age as put forward by Ramírez-Tannus et al (2021). The observed orbital distributions of OB stars might not be the exact end product of star formation; yet, they probably provide good enough starting points to compute their subsequent evolution and future fate.…”
Section: Main-sequence Ob Starsmentioning
confidence: 69%
“…With ample fuel available within the gas-rich protocluster environment, the protostellar masses (and luminosities) are expected to increase with time. Accretion will also affect the binary separation, which can increase or decrease depending on turbulence, magnetic field strength, and the presence of outflows, with magnetic fields promoting the formation of close high-mass binary systems (e.g., Lund & Bonnell 2018;Harada et al 2021;Ramírez-Tannus et al 2021).…”
Section: Discussionmentioning
confidence: 99%